Low-scatter galaxy cluster mass proxies for the eROSITA all-sky survey - Dominique Eckert; Alexis Finoguenov; Vittorio Ghirardini; Sebastian Grandis; Florian Kaefer; Jeremy Sanders; Miriam Ramos-Ceja (The Open Journal of Astrophysics, 2020)
The on-going X-ray all-sky survey with the eROSITA instrument will yield large galaxy cluster samples, which will bring strong constraints on cosmological parameters. In particular, the survey holds great promise to investigate the tension between CMB and low-redshift measurements. The current bottleneck preventing the full exploitation of the survey data is the systematics associated with the relation between survey observable and halo mass. Numerous recent studies have shown that gas mass and core-excised X-ray luminosity exhibit very low scatter at fixed mass. We propose a new method to reconstruct these quantities from low photon count data and validate the method using extensive eROSITA-like simulations. We find that even near the detection threshold of ~50 counts the core-excised luminosity and the gas mass can be recovered with 20-30% precision, which is substantially less than the scatter of the full integrated X-ray luminosity at fixed mass. When combined with an accurate calibration of the absolute mass scale (e.g. through weak gravitational lensing), our technique reduces the systematics on cosmological parameters induced by the mass calibration.